A feedforward loop within the thyroid-brown fat axis facilitates thermoregulation - Sun, Lijuan (2021)
Thyroid hormones (TH) control brown adipose tissue (BAT) activation and differentiation, but their subsequent homeostatic response following BAT activation remains obscure. This study aimed to investigate the relationship between cold- and capsinoids-induced BAT activation and TH changes between baseline and 2 hours post-intervention. Nineteen healthy subjects underwent 18F-fluorodeoxyglucose positron-emission tomography (18F-FDG PET) and whole-body calorimetry (WBC) after 2 hours of cold exposure (~14.5 °C) or capsinoids ingestion (12 mg) in a crossover design. Standardized uptake values (SUV-mean) of the region of interest and energy expenditure (EE) were measured. Plasma free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) were measured before and 2 hours after each intervention. Subjects were divided into groups based on the presence (n = 12) or absence (n = 7) of BAT after cold exposure. 12 of 19 subjects were classified as BAT-positive. Subjects with BAT had higher baseline FT3 concentration, baseline FT3/FT4 ratio compared with subjects without BAT. Controlling for body fat percentage, FT3 concentration at baseline was associated with EE change from baseline after cold exposure (P = 0.037) and capsinoids (P = 0.047). Plasma FT4 level significantly increased associated with reciprocal decline in TSH after acute cold exposure and capsinoids independently of subject and treatment status. Circulating FT3 was higher in BAT-positive subjects and was a stronger predictor of EE changes after cold exposure and capsinoids in healthy humans. BAT activation elevates plasma FT4 acutely and may contribute towards augmentation of thermogenesis via a positive feedback response.